9 Application of the boston children's hospital cardiac surgery technical performance score to intraoperative echocardiography in a designated tertiary centre in the united kingdom. (2nd February 2018) - Bellsham-Revell, H; Deri, A; Caroli, S; Durward, A; Miller, O; Mathur, S; Saundankar, J; Anderson, D; Austin, C; Salih, C; Pushparajah, K; Simpson, J
Abstract : Purpose: The Technical Performance Score (TPS) performed on pre-discharge echocardiograms developed by Boston Children's Hospital has been shown to correlate with surgical outcomes. We sought to assess the feasibility and applicability of this in intraoperative imaging in a UK congenital cardiac surgical centre. Methods: After training, intraoperative TPS (epicardial and/or transoesophageal) was instituted for all cardiac surgical cases. This was used to inform intraoperative discussions using the previously published scoring system. After the first year, we assessed the relationship between the TPS and basic clinical outcomes. Results: From 01/09/15 to 04/07/16 there were 272 TPS procedures in 251 operations. Seven patients had surgery with no documented TPS. Four patients had operations for which there is no current template available. TPS when leaving theatre was: optimal 156 (75%), adequate 34 (16%) and inadequate 18 (9%). Fourteen patients had further runs of cardiopulmonary bypass after an inadequate score, with nine then leaving theatre with an optimal score. There was no significant difference between extubation time for optimal/adequate and inadequate with a median (range) of 1 (0–26 days) and 2.5 (0–11 days) respectively. There were 9 deaths <30 days, none had had an inadequate score. Conclusions: Application of intraoperative TPS to a tertiary UK congenital heart surgical centre is feasible and provides a meaningful way of objectively recording intraoperative imaging-based assessment of surgical results. There was no significant difference in extubation times (although these can be affected by factors other than surgical result), nor did an 'inadequate' TPS score predict mortality.